A simple passive 390 mV ac/dc rectifier for energy harvesting applications. (November 2019) - Santiago Rodriguez, A; Garraud, N; Alabi, D; Garraud, A; Arnold, D P
Abstract: This paper reports a simple, discrete, ac/dc rectifier architecture intended for magnetic energy harvesters that functions with ac input voltages as low as 390 mVpk . The proposed four NMOS rectifier (4NR) employs cross-connected, saturated-load NMOS inverters. The circuit is completely passive, exhibits good low-voltage performance, consists of only four components for small footprint, and requires no additional blocking diode to prevent power flow from the load. At 2 Vpk input, the 4NR exhibits a power efficiency of 93 % and 400 μW of output power. The 4NR is also successfully connected to an off-the-shelf TI BQ25504 dc/dc converter + battery management chip and shown to charge both capacitor and lithium-ion battery energy storage reservoirs.